INFORMATION TECHNOLOGY PROJECT MANAGEMENT RISK ANALYSIS - Del Carpio Gallegos, Javier (2006)
It is shown a managerial proposal about IT Project management. In this way project managers will have a methodology that allow to make a plan to face risks and to get success.